Efficacy of concomitant therapy with ademetionine in antitumor drug therapy: A review - Nikolai A. Ognerubov (ZAO "Consilium Medicum", 2024)
Liver injury caused by antitumor therapy is a common disorder in patients with malignancies. It is due to the introduction of new innovative drugs into the treatment, which significantly increases the duration and quality of life, but also the frequency of side effects with liver damage of varying severity. The rate of hepatotoxicity during chemotherapy ranges from 5% to 100%. The spectrum of morphological changes in the liver is diverse and includes acute and chronic liver injury with damage to hepatocytes and outcome in fibrosis. The clinical features of the diagnosis of various types, variants, and phenotypes of drug-induced liver injury in the chemotherapy of solid tumors and hematological malignancies are addressed. The article reviews the literature on concomitant treatment with ademetionine to reduce metabolic disorders and hepatic toxicity caused by cytotoxic therapy. Clinical and biochemical effects persist for a long time after treatment. The results of using ademetionine to correct clinical symptoms such as fatigue are described in detail. The presented data supports a practical revision of the role of concomitant therapy with ademetionine to prevent and reduce the manifestations of hepatotoxicity induced by polychemotherapy. This approach contributes to a personalized approach to patients with malignancies, thereby significantly improving medical care and increasing the duration and quality of life.